AQ Announces Initiative Against Bill 171 - Alliance Quebec (AQ) (2001)

Brief on Bill 170 : An Act to Reform the Municipal Territorial Organization of the [Metropolitan] Regions of Montreal, Quebec and Outaouais - Alliance Quebec (AQ) (2000)
Alliance Quebec welcomes the opportunity to present our concerns on Bill 170 - An act to reform the municipal territorial organization of the metropolitain regions of Montreal, Quebec and Outaouais. We would also like to take this opportunity to thank the Quebec Liberal Party for undertaking this initiative to ensure that all Quebecers have an opportunity to publicly express their views on Bill 170. We would note that we have made an effort to be included in the hearings before the National Assembly commission studying the law and like so many others who oppose the Bill, have not been accepted to be heard.